Cardiac rehabilitation programme after transcatheter aortic valve implantation versus surgical aortic valve replacement: Systematic review and meta-analysis - Ribeiro G.S. (2017)
© European Society of Cardiology 2017.Background Aortic stenosis is a valvular heart disease characterised by fixed obstruction of the left ventricular outflow. It can be managed by surgical aortic valve replacement (sAVR) or transcatheter aortic valve implantation (TAVI). This review aimed to describe the evidence supporting a cardiac rehabilitation programme on functional capacity and quality of life in aortic stenosis patients after sAVR or TAVI. Methods The search was conducted on multiple databases from January to March 2016. All studies were eligible that evaluated the effects of a post-interventional cardiac rehabilitation programme in aortic stenosis patients. The methodological quality was assessed using the PEDro scale. Meta-analysis was performed separately by procedure and between procedures. The walked distance during the six-minute walk test (6MWD) and Barthel index were evaluated. The analysis was conducted in Review Manager. Results Five studies were included (292 TAVI and 570 sAVR patients). The meta-analysis showed that a cardiac rehabilitation programme was associated with a significant improvement in 6MWD (0.69 (0.47, 0.91); P < 0.001) and Barthel index (0.80 (0.29, 1.30); P = 0.002) after TAVI and 6MWD (0.79 (0.43, 1.15); P < 0.001) and Barthel index (0.93 (0.67, 1.18); P < 0.001) after sAVR. In addition, the meta-analysis showed that the cardiac rehabilitation programme promoted a similar gain in 6MWD (4.28% (-12.73, 21.29); P = 0.62) and Barthel index (-1.52 points (-4.81, 1.76); P = 0.36) after sAVR or TAVI. Conclusions The cardiac rehabilitation programme improved the functional capacity and quality of life in aortic stenosis patients. Patients who underwent TAVI benefitted with a cardiac rehabilitation programme similar to sAVR patients.